An evolutionary game analysis on price competition in recycling industry between large and small enterprises of China. Issue 2 (February 2023) - Yu, Zhang; Khan, Syed Abdul Rehman; Zia-Ul-Haq, Hafiz Muhammad; Ma, Tianshan; Sajid, Muhammad Jawad
This research aims to analyse and understand recycling phenomena and competition between large-scale and small-scale enterprises under different public attention. It mainly emphasizes service-providing behaviours to the consumers in the recycling industry, where recyclers are struggling to enhance their profits. The government strives to protect the environment by promoting an efficient recycling industry. As fast-growing waste products, the recyclers should achieve the advantage of number and be equipped with service capability for the consumers. Thus, this study employs an evolutionary game model to analyse the competition for waste products acquisitions between large and small recyclers. Due to a significant association between the service and acquisition waste product price for the consumers and recycling quantity, there is a strong mutual influence between the acquisition price of waste products and the price strategy-taken rate of large and small recyclers. Results also reveal that the market acquisition price and processing cost play a crucial role in recyclers' decision-making on setting prices for acquiring waste products from consumers. Furthermore, it is also found that waste products acquisition price and recyclers' processing cost are the key factors that affect large and small recyclers' recycling quantity.